ENHANCING ENGLISH SKILLS THROUGH CLIL METHODOLOGY IN HIGHER EDUCATION: A REVIEW ARTICLE - Hallasi-Ancori, Miozelit Ailuj (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
CLIL (Content and Language Integrated Learning) methodology has revealed its effectiveness and impact on English skills enhancement in university settings and is considered a paradigmatic pedagogical approach in higher education. This paper aimed to perform an exhaustive scientific literature review about the CLIL methodology's effect on university students’ English Skills (Listening, Speaking, Reading, and Writing) enhancement, among different academic disciplines. Therefore, a narrative bibliographic review article has been carefully performed out of a vast source of scientific work analysis and compilation, published in the last six years, which has been extracted from a well-known academic database such as Scopus, Scielo, Google Scholar, Web of Science, Eric, Semantic Scholar, among others. Results showed that the CLIL methodology highlights its relevance when implemented in higher education due to its effectiveness and impact on English skills. Therefore, it has become an essential tool for boosting meaningful learning and promoting contextualized content learning with better alignment with university students’ academic needs enabling them to face the globalized labor market. Consequently, this study has revealed CLIL benefits such as students’ English skills improvement and content knowledge; and challenges to overcome such as limited instructors’ preparation on the language, the content, and even the CLIL methodology.